2013
DOI: 10.1002/qj.2211
|View full text |Cite
|
Sign up to set email alerts
|

Estimating interchannel observation‐error correlations for IASI radiance data in the Met Office system†

Abstract: This article is published with the permission of the Controller of HMSO and the Queen's Printer for Scotland.The optimal utilisation of hyper-spectral satellite observations in numerical weather prediction is often inhibited by incorrectly assuming independent interchannel observation errors. However, in order to represent these observation-error covariance structures, an accurate knowledge of the true variances and correlations is needed. This structure is likely to vary with observation type and assimilation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
103
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(111 citation statements)
references
References 23 publications
7
103
1
Order By: Relevance
“…While these results show promise and provide useful guidance, further development is needed to apply these ideas with real observations in operational systems. This work is already underway (Weston, 2011;Pocock et al, 2012;Stewart et al, 2012).…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While these results show promise and provide useful guidance, further development is needed to apply these ideas with real observations in operational systems. This work is already underway (Weston, 2011;Pocock et al, 2012;Stewart et al, 2012).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Nevertheless, attempts have been made to quantify error correlation structure for a few different observation types such as Atmospheric Motion Vectors (Bormann et al, 2003) and satellite radiances (Sherlock et al, 2003;Stewart et al, 2009;Stewart, 2010;Stewart et al, 2012). Using diagnosed correlations such as these in an operational assimilation system is far from straightforward: early attempts by the UK Met Office using IASI and AIRS data have resulted in conditioning problems with the 4D-Var minimisation (Weston, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Inter-channel correlations have been calculated for observations from satellite instruments such as the Atmospheric Infrared Sounder (AIRS) and Infrared Atmospheric Sounding Interferometer (IASI) using the Desroziers et al diagnostic [12][13][14][15][16]. The literature shows that inter-channel observation errors are correlated and that including these errors in the assimilation leads to improved analysis accuracy, better forecast skill score and the inclusion of more observation information content [6,[16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Yet, this study may provide understandings of the potential analysis performance for the real-world error-correlated observations, and also, may suggest what instrument design would be favorable if we have options. Stewart et al (2013) showed that the diagnosed observationerror correlations for the 130 channels in the Infrared Atmospheric Sounding Interferometer (IASI) had a significant block diagonal structure of the error correlation matrix. This study indicated that estimating only the components which are known to have non-zero values performed better (Fig.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Desroziers et al (2005) proposed a method to diagnose the observation error correlations. Previous studies applied the Desroziers diagnostics and estimated the observation error correlations such as the inter-channel correlations of the satellite radiances (Garand et al 2007;Stewart et al 2013), vertical correlations of radiosondes (Lönnberg and Hollingsworth 1986), and horizontal correlations of the atmospheric motion vectors, sea-surface winds by satellite scatterometers, and radar data (Keeler and Ellis 2000;Bormann et al 2003). However, the observation error correlations, or off-diagonal components of the observation error covariance matrix, are not considered in the current operational numerical weather prediction (NWP) systems to the best of the authors' knowledge.…”
Section: Introductionmentioning
confidence: 99%